Leadership chronicles of a corporate sage five keys to becoming a more effective leader - Bethanis, Susan J. (Chicago Dearborn Trade Pub., 2004)
Executive coaching expert Bethanis presents a behind-the-scenes look into how executives become better leaders. Focused on the real-life reflections and struggles of a composite of the author's own corporate clients, the book is based on actual coaching conversations. Dr. Bethanis, the story's coach and narrator, offers timely questions and insights in a simple way, showing the five keys to becoming a corporate sage: high emotional intelligence; strong networking and influencing skills; a long-lasting vision; ability to coach others instead of doing everything yourself; and a global perspective.--From publisher description
Keywords: Leadership; Executive ability; Executives--Training of